Microbial Quality of Cool Water Washed Shell Eggs - Jones, D.R.; Musgrove, M.T.; Caudill, A.B.; Curtis, P.A.; Northcutt, J.K. (International Journal of Poultry Science, 2005)
A study was conducted to examine the effects of cool water washing on the microbial quality of shell eggs. Six dual tank wash water temperature schemes were examined for their ability to reduce naturally occurring aerobic bacteria and inoculated Salmonella Enteritidis (SE). The wash water schemes were: T1= 48.9oC; T2 = 48.9oC, 23.9oC; T3 = 48.9oC, 15.6oC; T4 = 23.9oC; T5 = 15.6oC; and T6 = 23.9oC, 15.6oC. All wash water tanks were maintained from 10.5-11.5 pH throughout the study. Eggs were exposed to the wash water temperature schemes in a pilot egg washer with recirculating wash water tanks. The total amount of time eggs were exposed to the wash water combinations was 60 s. Following washing, all eggs were sprayed with a 48.9oC, 200 ppm chlorine rinse solution. Eggs were stored and sampled for 9 wks. External aerobic populations were lowest for T1 (typical U.S. wash water configuration), followed by T2 and T3. Aerobic surface contamination was greatest in T5 eggs. All treatments reduced SE levels in a similar manner as detected by shell and membrane emulsion and egg contents pools after enrichment. Commercial application of cool water shell egg processing will be investigated to determine the potential of this technology to enhance the safety and quality of shell eggs.